Common Patterns in Contemporary Nepali Arts, Life and Society - Sharma, Yam Prasad (Journal of Fine Arts Campus, 2021)
There are common trends and patterns in contemporary Nepal arts, politics, society, culture and education along with other dimensions of life. Such similarities suggest the interconnectedness of diverse dimensions of reality. One area mirrors the other one. Looking at art, we can infer the life and culture of the people. Superstructure is reflected in the base; and the base has been reflected in superstructure. Hypocrisy, pretention and imitation are the common patterns of Nepali art, culture and life in contemporary context. Due to such features, the foundation of the nation is shaking. The things that need to remain in the foundation are drifting on the surface. The drama of art, agriculture, education and politics will not support life and survival. It is just for showing until the disaster takes place. When there will be critical and catastrophic situation, we are sure to be drowned. Before this apocalypse, it is necessary to do little things that are real which enhance our art and life, which add a little stone on the foundation of the civilization. This research paper analyzes contemporary Nepali artworks and links them to cultural, social and political dimensions of the contemporary context. This is qualitative research since it interprets arts and events, and the interpretations can be multiple.